2015
DOI: 10.1111/bcp.12589
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic comparison of anrukinzumab, an anti‐ IL‐13 monoclonal antibody, among healthy volunteers, asthma and ulcerative colitis patients

Abstract: AIMSAnrukinzumab is an anti-IL13 monoclonal antibody. The goals of this study are to characterize the pharmacokinetics of anrukinzumab in healthy volunteers and different disease states and to identify covariates. METHODSA population pharmacokinetic (PK) model was developed in NONMEM, using data from five clinical studies including healthy volunteers, asthma and ulcerative colitis (UC) patients. Different dosing regimens including different routes of administration were also included in the data. RESULTSThe PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…In 7 publications, the type or subtype of disease was associated with differences in pharmacokinetic parameters. [67,70,107,136,[144][145][146] One of possible reasons of such differences are differences in amount and turnover (RT, ksyn, kdeg, see section 4.2), and localization (and therefore the accessibility by mAb) of antigenic targets. The 4 studies of anticancer mAbs that reported different mAb clearances among types of tumour did not investigate pathophysiological reasons of such differences.…”
Section: Influence Of Diseasementioning
confidence: 99%
“…In 7 publications, the type or subtype of disease was associated with differences in pharmacokinetic parameters. [67,70,107,136,[144][145][146] One of possible reasons of such differences are differences in amount and turnover (RT, ksyn, kdeg, see section 4.2), and localization (and therefore the accessibility by mAb) of antigenic targets. The 4 studies of anticancer mAbs that reported different mAb clearances among types of tumour did not investigate pathophysiological reasons of such differences.…”
Section: Influence Of Diseasementioning
confidence: 99%
“…The reasons for this quite “absolute” failure of anti-IL-13 treatment are not easily understood (38). Accelerated clearance of anrukinzumab was reported in UC patients in comparison to healthy volunteers or patients with asthma (39). This implies that a suboptimal dose may have been used in the UC trials.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Because the levels and production of IP-10, as well as its interaction with BMS-986184, may be different in patients with UC compared with healthy participants, dosage projections for patients with UC must be approached with caution. Finally, it should be noted that clearance of mAbs is typically faster in patients with UC than in healthy volunteers, 31,32 and thus consideration must be taken when selecting therapeutic doses for patients.…”
Section: Discussionmentioning
confidence: 99%